Endothelial Glycocalyx Disorders May Be Associated With Extended Inflammation During Endotoxemia in a Diabetic Mouse Model - Sampei, So; Okada, Hideshi; Tomita, Hiroyuki; Takada, Chihiro; Suzuki, Kodai; Kinoshita, Takamasa; Kobayashi, Ryo; Fukuda, Hirotsugu; Kawasaki, Yuki; Nishio, Ayane; Yano, Hirohisa; Muraki, Isamu; et al. (Frontiers in Cell and Developmental Biology, 2021)
In diabetes mellitus (DM) patients, the morbidity of infectious disease is increased, and these infections can easily progress from local to systemic infection. Sepsis is a characteristic of organ failure related to microcirculation disorders resulting from endothelial cell injury, and whose most frequent comorbidity in patients is DM. The aim of the present study was to evaluate the influence of infection on DM-induced microvascular damage on inflammation and pulmonary endothelial structure using an experimental endotoxemia model. Lipopolysaccharide (LPS; 15 mg/kg) was injected intraperitoneally into 10-week-old male C57BLKS/J Iar−+leprdb/leprdb (db/db) mice and into C57BLKS/J Iar−m+/+leprdb (db/+) mice, which served as the littermate nondiabetic control. At 48 h after LPS administration, the survival rate of db/db mice (0%, 0/10) was markedly lower (P < 0.05) than that of the db/+ mice (75%, 18/24), whereas the survival rate was 100% in both groups 24 h after LPS administration. In control mice, CD11b-positive cells increased at 6 h after LPS administration; by comparison, the number of CD11b-positive cells increased gradually in db/db mice until 12 h after LPS injection. In the control group, the number of Iba-1-positive cells did not significantly increase before and at 6, 12, and 24 h after LPS injection. Conversely, Iba-1-positive cells continued to increase until 24 h after LPS administration, and this increase was significantly greater than that in the control mice. Expression of Ext1, Csgalnact1, and Vcan related to endothelial glycocalyx synthesis was significantly lower in db/db mice than in the control mice before LPS administration, indicating that endothelial glycocalyx synthesis is attenuated in db/db/mice. In addition, ultrastructural analysis revealed that endothelial glycocalyx was thinner in db/db mice before LPS injection. In conclusion, in db/db mice, the endothelial glycocalyx is already injured before LPS administration, and migration of inflammatory cells is both delayed and expanded. This extended inflammation may be involved in endothelial glycocalyx damage due to the attenuation of endothelial glycocalyx synthesis.